ChemInform Abstract: Reductive Cyclization and Petasis‐Like Reaction for the Synthesis of Functionalized γ‐Lactams. Issue 34 (August 2015) - Wu, Peng; Petersen, Michael Aaxman; Cohrt, A. Emil; Petersen, Rico; Clausen, Mads H.; Nielsen, Thomas E.
Abstract N‐substituted β, γ‐dihydroxy‐γ‐lactams are convenient substrates for Petasis‐like reactions with boronic acids.